Genome-wide identification and expression profiling of the SWEET family in Actinidia polygama (Sieb. & Zucc.) Maxim. - Li Chen; Hui-Fang Song; Jia-Xin Liu; Xu-Xin Jiang; Jun Ai; Zhen-Xing Wang; Yun-Peng Wang (Fruit Research)
Sugar was transported from photosynthetic source cells to sink cells, sugar efflux transporter protein (sugars will eventually be exported to transporters, SWEETs) play an important role in the process. Although SWEET family members had been identified in many plants, transcriptome or genomics analysis of Actinidia polygama SWEET genes remains uncharacterized. In this study, 14 SWEET genes of Actinidia polygama were identified by protein Blast. The structural characteristics of SWEET genes showed that the number of amino acids encoded by the gene family was between 233 and 304, the relative molecular weight was between 25,918.83 and 33,192.12, the isoelectric point was within the range of 6.96 to 9.71, 14 ApSWEET from Actinidia polygama and the known grape and Arabidopsis SWEETs were divided into four clades (I, II, III, and IV) according to the phylogenetic relationships. The gene structure analysis showed that most of ApSWEET genes have six exons and five introns except ApSWEET5 and ApSWEET14. All ApSWEET proteins also contained P-loop, MtN3-slv, and transmembrane domain. Expression patterns of 14 ApSWEET in different organs and at different fruit developmental stages were analyzed. ApSWEET1 and ApSWEET5 exhibited tissue-speciﬁc expression, whereas other genes were more ubiquitously expressed. ApSWEET1, ApSWEET10, and ApSWEET11 exhibited higher expression in fruit. The results of this study provide insights into the characteristics of the SWEET genes in Actinidia polygama and may serve as a basis for further functional studies of such genes.